Orientational order parameter in a-N2 from x-ray data - Galtsov, N. N.; Klenova, O. A.; Strzhemechny, M. A. (ФІЗИКА НИЗЬКИХ ТЕМПЕРАТУР, 2002)
A method is suggested and validated for the deduction of orientational order parameter values h in molecular crystals consisting of diatomics directly from integrated x-ray diffraction intensities. This method is applied to pure solid nitrogen in its a phase. It is shown that to within a good accuracy the integrated intensity of a superstructure reflection is proportional to h2. The h values determined from x-ray powder diffraction measurements agrees well with the values obtained by NQR and NMR.